Intra-specific variation in genome size in maize: Cytological and phenotypic correlates - Realini, Maria Florencia (2016)
Genome size variation accompanies the diversification and evolution of many plant species. Relationshipsbetween DNA amount and phenotypic and cytological characteristics form the basis of most hypotheses thatascribe a biological role to genome size. The goal of the present research was to investigate the intra-specific variationin the DNA content in maize populations from Northeastern Argentina and further explore the relationship betweengenome size and the phenotypic traits seed weight and length of the vegetative cycle. Moreover, cytological parameterssuch as the percentage of heterochromatin as well as the number, position and sequence composition ofknobs were analysed and their relationships with 2C DNA values were explored. The populations analysed presentedsignificant differences in 2C DNA amount, from 4.62 to 6.29 pg, representing 36.15 % of the inter-populational variation.Moreover, intra-populational genome size variation was found, varying from 1.08 to 1.63-fold. The variation inthe percentage of knob heterochromatin as well as in the number, chromosome position and sequence composition ofthe knobswas detected among and within the populations. Although a positive relationship between genome size andthe percentage of heterochromatin was observed, a significant correlation was not found. This confirms that othernon-coding repetitive DNA sequences are contributing to the genome size variation. A positive relationship betweenDNA amount and the seed weight has been reported in a large number of species, this relationship was not found inthe populations studied here. The length of the vegetative cycle showed a positive correlation with the percentage ofheterochromatin. This result allowed attributing an adaptive effect to heterochromatin since the length of this cyclewould be optimized via selection for an appropriate percentage of heterochromatin.